Complex traffic flow that allows as well as hampers lane-changing intrinsically contains social-dilemma structures. (27th February 2018) - Iwamura, Yoshiro; Tanimoto, Jun
Abstract: To investigate an interesting question as to whether or not social dilemma structures can be found in a realistic traffic flow reproduced by a model, we built a new microscopic model in which an intentional driver may try lane-changing to go in front of other vehicles and may hamper others' lane-changes. Our model consists of twofold parts; cellular automaton emulating a real traffic flow and evolutionary game theory to implement a driver's decision making-process. Numerical results reveal that a social dilemma like the multi-player chicken game or prisoner's dilemma game emerges depending on the traffic phase. This finding implies that a social dilemma, which has been investigated by applied mathematics so far, hides behind a traffic flow, which has been explored by fluid dynamics. Highlight – Complex system of traffic flow with consideration of driver's decision making process is concerned. – A new model dovetailing cellular automaton with game theory is established. – Statistical result from numerical simulations reveals a social dilemma structure underlying traffic flow. – The social dilemma is triggered by a driver's egocentric actions of lane-changing and hampering other's lane-change.